An air-stable microwire radial heterojunction with high photoconductivity based on a new building block1. Issue 23 (21st June 2015) - Zhang, Jianfeng; Wang, Jinshan; Xu, Xinjun; Chen, Shiyan; Zhang, Qinglin; Yao, Chuang; Zhuang, Xiujuan; Pan, Anlian; Li, Lidong
<x xml:space="preserve">Abstract</x> A one-dimensional radial heterojunction structure based on a new electron-donating unit (dithienopyrazine) has been achieved with a high photoconductivity.